2001
DOI: 10.1086/319593
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Toxocara as a Possible Risk Factor for Asthma: A Clinic-Based Case-Control Study

Abstract: The zoonotic ascarid Toxocara has been suggested as a possible etiologic agent of asthma. We conducted a clinic-based case-control study to examine whether the zoonotic infection acquired by ingesting Toxocara eggs is associated with asthma in children. Blood samples were collected from children aged 2-15 years, 95 of whom had asthma and 229 of whom did not have asthma. Risk factors for asthma and Toxocara infection were assessed by a questionnaire given to each child's parent or legal guardian. Blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
5
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 19 publications
4
75
5
4
Order By: Relevance
“…More recent animal studies have shown compromised lung function in mice infected with other nematodes (Buijs et al 1995;Pinelli et al 2005). Furthermore, results from human studies also support a more specific association between Toxocara infection and asthma in low and middle income countries (Feldman and Parker, 1992;Buijs, 1994;Buijs, 1997;Oteifa, 1998;Chan, 2001;Sharghi, 2001;Kuk, 2006). Finally, a report using the full national sample from NHANES III was the first to show a distinct, independent association between previous Toxocara infection and lung function in a national population-based study, with a 73 mL decreased FEV 1 among the infected participants (Walsh, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…More recent animal studies have shown compromised lung function in mice infected with other nematodes (Buijs et al 1995;Pinelli et al 2005). Furthermore, results from human studies also support a more specific association between Toxocara infection and asthma in low and middle income countries (Feldman and Parker, 1992;Buijs, 1994;Buijs, 1997;Oteifa, 1998;Chan, 2001;Sharghi, 2001;Kuk, 2006). Finally, a report using the full national sample from NHANES III was the first to show a distinct, independent association between previous Toxocara infection and lung function in a national population-based study, with a 73 mL decreased FEV 1 among the infected participants (Walsh, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Instead, more insidious chronic disease involving the lungs, vasculature, and central nervous system may be more prevalent and, thus, of greater public health significance (Hotez and Wilkins, 2009). Diminished lung function has been associated with Toxocara infection in animal models, as have infections with other nematodes whose development includes migration across pulmonary tissues (Pritchard et al 1983;Buijs, 1995;Pinelli, 2005 (Feldman and Parker, 1992;Buijs, 1994;1997;Oteifa, 1998;Chan, 2001;Sharghi, 2001;Kuk, 2006), but how this might translate to a high income country with significant health disparities is unknown. Finally, a previous study examining the NHANES III sample population identified a strong association between Toxocara infection and diminished lung function that was robust to many other contributing factors to both toxocariasis and lung function including gender, ethnicity, and rural residence (Walsh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Which effect predominates in a particular human population depends on the concurrence of several factors, among them intensity of the infection [11], which in turn is probably determined by genetic factors controlling the strength of the protective immunity and the degree of susceptibility to parasite immunomodulation [12]. Positive associations between asthma and helminthiases are expected not only in some urban populations of middleincome countries where they are partially controlled and deworming programs are permanent [13], but also in developed countries where these infections are still present [14]. Therefore, it is neither surprising nor contradictory to find some studies showing positive associations between helminth infections and allergy [15] and others detecting negative associations.…”
Section: The Dual Effect Of Helminth Infectionsmentioning
confidence: 99%
“…Children are particularly prone to infection because they are exposed to the eggs in sandboxes and playgrounds contaminated with dog and cat feces [11•]. The prevalence rate of toxocariasis, which is based on serologic studies that measure antibodies to T. canis antigens, among inner city blacks living in Connecticut cities was found to be 10 % and even higher among inner city Hispanics [12]. The prevalence among socioeconomically disadvantaged blacks in the American South was as high as 30 % between 1971 and 1973 [13]; however, it was recently estimated that approximately 21 % of blacks are seropositive [14].…”
Section: Toxocariasis In the United Statesmentioning
confidence: 99%